Effects of Somatic Mutations Are Associated with SNP in the Progression of Individual Acute Myeloid Leukemia Patient: The Two-Hit Theory Explains Inherited Predisposition to Pathogenesis - Soyoung Park; Youngil Koh; Sung-Soo Yoon (Genomics & Informatics)
This study evaluated the effects of somatic mutations and single nucleotide polymorphisms (SNPs) on disease progression and tried to verify the two-hit theory in cancer pathogenesis. To address this issue, SNP analysis was performed using the UCSC hg19 program in 10 acute myeloid leukemia patients (samples, G1 to G10), and somatic mutations were identified in the same tumor sample using SomaticSniper and VarScan2. SNPs in KRAS were detected in 4 out of 10 different individuals, and those of DNMT3A were detected in 5 of the same patient cohort. In 2 patients, both KRAS and DNMT3A were detected simultaneously. A somatic mutation in IDH2 was detected in these 2 patients. One of the patients had an additional mutation in FLT3, while the other patient had an NPM1 mutation. The patient with an FLT3 mutation relapsed shortly after attaining remission, while the other patient with the NPM1 mutation did not suffer a relapse. Our results indicate that SNPs with additional somatic mutations affect the prognosis of AML.